2009
DOI: 10.1007/s10238-009-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating pentraxin 3 levels are higher in metabolic syndrome with subclinical atherosclerosis: evidence for association with atherogenic lipid profile

Abstract: Metabolic syndrome is characterized by increased cardiovascular risk. Pentraxin 3 (PTX3), an acute phase protein, is involved in atherosclerosis. No information is available on PTX3 plasma concentrations in metabolic syndrome and on its associations with metabolic alterations and subclinical atherosclerosis. The aim of this study was to assess PTX3 plasma levels in metabolic syndrome patients compared to control subjects and their potential associations with anthropometric and clinical components of the syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
61
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 30 publications
(40 reference statements)
7
61
3
4
Order By: Relevance
“…Kardas and cols. (24) reported that PTX-3 levels were higher in obese children and adolescents with MetS and CVD, and that these levels were positively correlated with TG and negatively correlated with HDL-C levels (24,25). It was suggested that PTX3 levels may increase in order to confer protection against cardiac tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kardas and cols. (24) reported that PTX-3 levels were higher in obese children and adolescents with MetS and CVD, and that these levels were positively correlated with TG and negatively correlated with HDL-C levels (24,25). It was suggested that PTX3 levels may increase in order to confer protection against cardiac tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that PTX3 levels may increase in order to confer protection against cardiac tissue damage. PTX3 binds to activated platelets and reduces inflammation in the cardiovascular bed (12), and might be a novel marker for subclinical atherosclerosis (25). These findings suggested that both PTX-3 and RBP-4 may be used to predict inflammatory status in MetS instead of hsCR, which is a well-known acute phase inflammatory marker.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, negative correlations between concentrations of plasma PTX3 protein and triglycerides and BMI and lower PTX3 values in individuals with metabolic syndrome were described in a large population of subjects (34,44). However, some recent studies (30,45) disagree with these associations, reporting a positive link between PTX3, obesity, and some cardiovascular risk factors that associates the inflammatory function of this pentraxin with a worse cardiovascular profile. There is little information about PTX3 gene expression in AT, although PTX3 mRNA levels are higher in the white AT of genetically obese (ob/ob) and obese diabetic (db/db) mice than in controls (1).…”
mentioning
confidence: 99%
“…W ogólnej populacji osób zdrowych nie obserwuje się związku PTX3 z profilem lipidowym [14]. Koreluje ona natomiast dodatnio ze stężeniami cholesterolu frakcji LDL i triglicerydów u osób z zaburzeniami gospodarki węglowo-danowej, insulinoopornością, zespołem metabolicznym i cukrzycą typu 2 [15][16][17].…”
Section: Pentraksynaunclassified